Aavarana : the Veil - Bhyrappa, S.L.; Balakrishna, Sandeep(tr.) (New Delhi Rupa publication, 2014)
Aavarana: The Veil raises pertinent and searching questions about religion, liberalism and identity, and highlights the importance of unshackling oneself from the bonds of false knowledge.
Keywords: Hindi fiction; Religions; Liberalism; Identity (Philosophical concept); Kannada fiction; India